2015
DOI: 10.1007/s00787-015-0695-3
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of adolescents before and after the death of a parent or sibling

Abstract: The death of a parent or sibling (family bereavement) is associated with mental health problems in approximately, 25 % of the affected children. However, it is still unknown whether mental health problems of family-bereaved adolescents are predicted by pre-existing mental health problems, pre-loss family functioning, or multiple bereavements. In this study, a prospective longitudinal assessment of change in mental health following bereavement was done in a large representative sample from the ‘Tracking Adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 44 publications
5
78
0
5
Order By: Relevance
“…21 Although they are capable of rational thinking, adolescents, like adults, nonetheless benefit from additional explanation and discussion in addition to emotional support. Although they often turn to peers for support and assistance in many situations, after the death of a close family member or friend, they can benefit from the additional physical and emotional presence of adults.…”
Section: Adolescentsmentioning
confidence: 99%
“…21 Although they are capable of rational thinking, adolescents, like adults, nonetheless benefit from additional explanation and discussion in addition to emotional support. Although they often turn to peers for support and assistance in many situations, after the death of a close family member or friend, they can benefit from the additional physical and emotional presence of adults.…”
Section: Adolescentsmentioning
confidence: 99%
“…This data can also be seen as the prospect of subsequent studies on children' psychological trauma for violence or witnessing violence (American Psychiatric Association, 2013;McDonaldet al, 2016). The death of parents marked an emotional and psychological turning point in the life of a human being (Stikkelbroek, Bodden, Reitz, Vollebergh & van Baar, 2016;Gutiérrez, Menendez, Jiang, Hernandez, Miller & Rosengren, 2019). For children and adolescents, losing a parent can be a chronic non-healing wound (Abrams, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Birenbaum 7 found that adolescents who lost a sibling to cancer were at higher risk of developing physiologic and psychosocial symptoms than other age groups. Stikkelbroek and colleagues 8 found that adolescents had more internalizing problems after the loss of a sibling than loss of a parent. For some adolescents loss of a sibling may facilitate psychological growth with reported feelings of being “more mature” than most of their peers.…”
Section: Adolescents’ Responsesmentioning
confidence: 99%